Bioinspired self-similar all-dielectric antennas: probing the effect of secondary scattering centres by Raman spectroscopy. Issue 7 (29th September 2020) - Alessandri, Ivano; Carletti, Luca; Ferroni, Matteo; De Angelis, Costantino; Vassalini, Irene
Abstract : The role of secondary scattering centres in surface light management of self-similar optical antennas is investigated by microRaman spectroscopy. Abstract : All-dielectric optical antennas offer unique advantages in fabrication of highly reproducible Raman probes and light management at the meso- and nano-scale. Hot-spot engineering is a key step for enhancing the local field and promoting light channelling from far- to near-field. However, unlike the case of plasmonic antennas, hot-spot design and implementation in all-dielectric systems is still largely underdeveloped. Inspired by building-up principles that govern absorption, trapping and scattering of visible light in a variety of biological structures and guided by finite element optical simulations, here we explored the potential of self-similar dielectric optical antennas in light coupling with Mie-type modes. The systems investigated were based on the combination of primary and secondary antennas, made of micron- and nano-sized TiO2 nanoshells. Different types of configurations, including randomly and hierarchically organized antennas were tested. Raman experiments revealed that hierarchically ordered structures offer superior SERS performances in terms of field enhancement and reproducibility in comparison to the randomly arranged counterparts, which are in turn more efficient, yet less reproducible, than simple micro-sized antennas taken as a reference. These results open the door to further investigations in view of developing next-generation platforms for SERS and photocatalysis.